A STUDY ON INVESTORS PERCEPTION TOWARDS SYSTEMATIC INVESTMENT PLAN (SIPS): AN ALTERNATE INVESTMENT OPTION (International Journal of Food and Nutritional Sciences, 2022)
An investment is an asset acquired with the goal of generating income or appreciation. In the contemporary era of globalization, there is large number of investment avenues available for the investors with different risk return characteristics. Mutual Funds are one among them. Mutual funds are the money-managing institutions that pool money from the public and invest it in diversified portfolio of assets, such as in stocks, bonds and other securities.The plan of investing the same amount of money every month over an extended period of time regardless of whether market conditions are up or down makes the investment in SIPs unique from other avenues of investment. Mutual Fund gives an individual four good reasons for investing through SIP